2020
DOI: 10.1186/s12885-020-07649-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG15 in various cancers: a meta and bioinformatic analysis

Abstract: Background The snoRNA host gene SNHG15 produces a long non-coding RNA (lncRNA) with a short half-life and has been reported to be dysregulated in multiple cancers and has recently been found to be correlated with tumour progression. Therefore, this meta-analysis was performed to evaluate the generalised prognostic role of small nucleolar RNA host gene 15 (SNHG15) in malignancies, based on variable data from different studies. Methods Four public da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Accumulating studies have shown that lncRNAs were abnormally expressed in various cancers, and function as oncogene or tumor suppressor based on these expression level, participate in the initiation and progression of cancer. Previous meta-analyses have indicated that DLX6-AS1 [ 40 ], PVT1 [ 41 ], SNHG15 [ 22 ] and GHET1 [ 24 ] are related to the clinicopathological features and prognosis of various cancers. These evidences indicated that lncRNA may be a specific prognostic biomarker and therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have shown that lncRNAs were abnormally expressed in various cancers, and function as oncogene or tumor suppressor based on these expression level, participate in the initiation and progression of cancer. Previous meta-analyses have indicated that DLX6-AS1 [ 40 ], PVT1 [ 41 ], SNHG15 [ 22 ] and GHET1 [ 24 ] are related to the clinicopathological features and prognosis of various cancers. These evidences indicated that lncRNA may be a specific prognostic biomarker and therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The total scores for different studies ranged from 0 to 9. The study was considered to be high quality if the score was > 6 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…SNHG15 is an lncRNA which plays critical roles in the development and progression of various cancers through regulation of Akt/mTOR signaling [153,154]. It has been reported as a prognostic marker in colorectal and liver cancers [155,156].…”
Section: Snhg15mentioning
confidence: 99%
“…When SNHG15 is produced in higher quantities, it is associated with tumorigenic functions, including proliferation and metastasis in a variety of cancer types [ 22 , 23 , 24 ]. SNHG15 has been linked to lower survival in a lot of human malignancies, including breast cancer, colorectal cancer, gastric cancer, glioma, hepatocellular cancer, lung cancer, osteosarcoma, ovarian cancer, pancreatic cancer, renal cell carcinoma and thyroid cancer [ 25 , 26 ]. In pancreatic cancer tissue samples and cell lines, its expression was higher than expected, suggesting that it has pro-oncogenic functions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%